Incidence of Velopharyngeal Insufficiency after Primary Cleft Palate Repair: A 27-Year Assessment of One Surgeon's Experience - Jung, Chan Woo; Seo, Hyung Joon; Choi, Ye Seul; Bae, Yong Chan (Archives of Plastic Surgery, 2024)
Background Velopharyngeal insufficiency (VPI) is a major complication of cleft palate repair. The purpose of this study was to evaluate the incidence and predictive factors of VPI after cleft palate repair based on 27 years of one surgeon's experience.Methods Medical records were retrospectively reviewed for 652 patients who underwent cleft palate repair between 1995 and 2021. After exclusion of those with other syndromes or developmental disorders, the study included 374 patients with sufficient follow-up until the age of 4 years, when language evaluation was possible. VPI status was categorized through subjective and objective tests into normal, VPI, and borderline. We analyzed potential differences in VPI incidence by multiple factors. Factors with significance were analyzed to confirm the relationships between subvariables.Results Of the 374 patients, 311 (83.2%) exhibited normal pronunciation, 51 (13.6%) had VPI, and 12 (3.2%) were borderline. Primary cleft palate repair performed after 18 months was associated with a higher incidence of VPI than repair conducted before 18 months (p = 0.005). The incidence of VPI was higher in cases of submucous cleft palate than in the other types based on the Veau classification (p = 0.011). However, in the multivariable analysis, only the submucous type showed statistically significant results (p = 0.026).Conclusion A total of 374 people underwent primary cleft palate repair, and 13.6% of those with VPI required secondary therapy. The incidence of VPI was relatively high among patients with primary cleft palate repair after 18 months and patients with submucous cleft palate.
Keywords: cleft palate; velopharyngeal insufficiency; risk factor